Banisteriopsis caapi, a Forgotten Potential Therapy for Parkinson's Disease?. Issue 1 (6th October 2015) - Djamshidian, Atbin; Bernschneider‐Reif, Sabine; Poewe, Werner; Lees, Andrew J.
Abstract: Banisteriopsis caapi, a liana indigenous to the Amazon basin with metagnomigenic properties and possible anti‐depressant effects is one of the natural sources of harmala alkaloids. A summary of early trials with extracts of Banisteriopsis caapi and Peganum harmala (from which harmine was first isolated) in the 1920s and 1930s on various forms of parkinsonism is given as well as a brief overview of the known pharmacological properties of harmine. Despite its earlier abandonment because of perceived weaker efficacy than solanaceous alkaloids like scopolamine and hyoscine we propose that harmine should be reconsidered as a potential rapidly acting anti‐Parkinsonian agent.